Business Competitiveness of Small Medium Enterprise in Pandemic Era Covid-19 (Case Study on Souvenir Business in the Special Economic Area of Tourism Likupang, North Sulawesi Province, Indonesia) - Kawulur, Arie Frits; Mawitjere, Noula; Kawulur, Hisky (AIBPM Publisher, 2021)
This study aims to describe the small medium enterprises that grow and exist in